Metabolism of Deoxycorticosterone by Human Fecal Flora - Bokkenheuser, Victor D. (1975)
21-Dehydroxylation, a feature of metabolism of corticoids in humans, was observed in mixed cultures of fecal flora of normal individuals on a Western diet. The model substrate, 11-deoxycorticosterone (DOC), was metabolized to 3α-21-dihydroxy-5β-pregnan-20-one (THDOC), 3α-hydroxy-5β-pregnan-20-one (pregnanolone), and to two unidentified structures, metabolites X and Y. DOC was not metabolized in all media supporting growth of fecal flora. Conversion required an initial pH between 6.0 and 8.0. 21-Dehydroxylation occurred within 4 days of incubation in media inoculated with 10(-1) to 10(-7) fecal suspensions. In higher dilutions, containing obligatory anaerobes only, DOC was converted to metabolite X and sometimes also to metabolite Y. The yield of pregnanolone was related to the promptness with which the specimen was processed, to the presence of cysteine in the medium, and to the concentration of substrate (optimum, 16 to 64 μg of DOC per ml). The yield of THDOC was related to the delay in the processing of the specimen, the concentration of substrate (maximum at 256 μg/ml), and aeration of the culture. Pure cultures of aerobic organisms of fecal origin either failed to metabolize DOC or converted it to metabolite Y. Pure cultures of fecal anaerobes converted DOC to metabolite X and sometimes also to metabolite Y. Neither THDOC nor pregnanolone was produced by pure cultures.